AKHLAK MURID KEPADA GURU (KAJIAN CERAMAH BUYA YAHYA) - Nikmah, Akhodhatun (Penerbit Widina, Widina Media Utama, 2024)
Seeking knowledge is important for humans to survive in this world and the afterlife. Knowledge is like a light in the darkness, a guide for charity. On the other hand, there are things that really need to be paid attention to because no matter how high knowledge resides, it will not be good if manners and morals are marginalized. Therefore, through studying Buya Yahya's lectures, we find out about the key to gaining knowledge, on the al Bahjah TV YouTube channel entitled